Effects of inosine monophosphate and exercise training on neuronal nitric oxide synthase in the mouse brain. (24th August 2020) - Tomiga, Yuki; Sakai, Kazuya; Nakashima, Shihoko; Uehara, Yoshinari; Kawanaka, Kentaro; Higaki, Yasuki
Highlights: IMP decreased nNOS in only ventral, but not in dorsal hippocampus. In ventral hippocampus, nNOS and CREB activity was negatively correlated. IMP decreased nNOS in cerebellum, but not in cerebral cortex and olfactory bulb. Exercise, either alone or combined with IMP, had no effects on brain nNOS. Abstract: Recently, the purine nucleoside inosine has been demonstrated to have several neuroprotective effects. Similarly, exercise training has well-known beneficial effects on mental health and cognitive function. Neuronal nitric oxide synthase (nNOS) is a key neuronal messenger in several brain regions, and the downregulation of nNOS has been shown to improve brain function. However, whether inosine and exercise training have combined effects on nNOS pathway-related proteins in the brain remains unknown. We found, for the first time, that inosine monophosphate (IMP), which is a precursor of inosine, decreases nNOS levels in the ventral hippocampus (vHp) and the cerebellum (Ce), but not in the dorsal hippocampus (dHp). In the vHp, the phosphorylation of cAMP response element-binding protein (CREB) was also upregulated, which negatively correlated with nNOS protein levels. In the cerebral cortex (Cx), no significant activation of the nNOS pathway was observed. In the dHp, vHp, Cx, and Ce, no interactions between the effects of IMP and exercise on nNOS protein and CREB phosphorylation levels were observed. The phosphorylation of nNOS was regulated by the phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt) pathway. Although IMP induced minor changes in Akt phosphorylation, nNOS phosphorylation was unchanged by either IMP or exercise. In conclusion, in the vHp, which is associated with emotional behavior, IMP decreased nNOS levels and activated CREB, suggesting that IMP can elicit anxiolytic effects.